ALTERNATION OF HEMATOLOGICAL AND SERUM BIOCHEMICAL PROFILES IN DOGS NATURALLY INFECTED WITH HEPATOZOON CANIS IN SOUTH WESTERN GUJARAT, INDIA - B.R. Maharana; Binod Kumar; B. J. Thakre; N. D. Hirani; T. K. Patbandha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study represents Hepatozoon canis infection in three among seventy eight dogs referred to Teaching Veterinary Clinical Complex (TVCC), Veterinary College, Junagadh from January to April 2013 with prior history of anorexia, anemia, depression and difficulty in locomotion. Significant clinical findings included higher body temperature (106oF), enlarged lymph nodes and congested mucus membrane. Blood smears were stained with Giemsa stain revealed capsule shaped gametocytes of H. canis in the cytoplasm of approximately 15 to 20% circulating neutrophils. This is the first time documentation of hepatozoonosis in dogs from south western Gujarat, India and hence placed on record.